On the geometric degree of the tangent bundle of a smooth algebraic variety - Jeronimo, Gabriela Tali (2025)
We present bounds for the geometric degree of the tangent bundle and the tangential variety of a smooth affine algebraic variety V in terms of the geometric degree of V. We first analyze the case of curves, showing an explicit relation between these degrees. In addition, for parametric curves, we obtain upper bounds that are linear in the degree of the given curve. In the case of varieties of arbitrary dimension, we prove general upper bounds for the degrees of the tangent bundle and the tangential variety of V that are exponential in the dimension or co-dimension of V, and a quadratic upper bound that holds for varieties defined by generic polynomials. Finally, we characterize the smooth irreducible varieties with a tangent bundle of minimal degree.